A study of the effects of total prostatectomy on urethral function of the dog : a thesis ... for the degree of Master of Veterinary Science in Surgery. - Bergman, Marcia McMurdy (Massey University, 1974)
The function of the proximal urethra was studied in twelve dogs both before and after prostatectomy by means of repeated intraurethral pressure recordings and micturating cystograms. The animals were destroyed at times from one to three months after surgery and their pelvic urethrae were studied histologically and compared with a further group of intact dogs. Throughout the experiments, a series of routine urine chemical, physical and bacteriological tests and blood chemical and cytological examinations were performed. In addition, daily observations were made of the clinical state of urinary control. A general pattern of intraurethral pressure was found to exist. Although individual variations occurred, the pattern recorded from a given animal was reproducible. In general, pressures were higher within the penile urethra than within the pelvic portion. A small pressure rise occurred at the bladder neck and another near the membranous and prostatic urethral junction. Preoperative intraurethral pressure was relatively constant within the membranous urethra. Micturating cystography revealed the prostatic urethra to be a distensible structure and the penile urethral lumen was generally narrower than the pelvic region both before and after surgery. Following prostatectomy, lower pressures were recorded throughout the pelvic urethra. Mean pre- and postoperative pressures at specific locations were subjected to statistical comparison and a significantly lower pressure was found following surgery at only one of the areas considered, that one near the mid-pelvic urethra. Pressure recordings performed soon after surgery were found to be invalid, probably due to postoperative swelling within the urethra. Areas of postoperative stricture formation, when they occurred, were marked by spikes on the pressure tracing. The histological structure of the pelvic urethra was characterized by a predominant striated muscle component extending from the caudal aspect of the prostate to the urethral bulb. Smooth muscle fibers of the prostate were continuous cranially with the bladder and caudally with the membranous urethra where they formed a minor portion of the wall. After surgical removal of the gland, striated muscle fibers constituted the main urethral muscular component. A highly vascular submucosal layer was conspicuous throughout the pelvic urethra. Diagrams of urethral muscular arrangement were composed from a study of the intact and prostatectomized animals. There were few clinical complications following the initial recovery period after prostatectomy. One dog exhibited mild stress incontinence. Two others developed urethral strictures. All animals were in good physical condition when electively destroyed. The results of the experiment suggest that the prostatic urethra is not an essential structure for urine control although the slightly higher urethral pressures in the caudal prostatic urethra where there is both a smooth and striated muscle component, imply that this region normally plays some role in urethral closure. The function of striated muscle tone in urinary control is probably increased after prostatectomy.
Keywords: Prostate; Urethra; Dogs; Surgery